1987
DOI: 10.1002/sia.740100706
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation and preferential sputtering in CoNi alloys: Computer simulation of Auger spectra

Abstract: The phenomena of surface segregation and preferential sputtering have been investigated in the Co-Ni alloy system where previous results have been contradictory. Six alloys covering the whole solid solution range were annealed at 853 K and quenched to give equilibrium segregated surfaces. Computer simulation methods were employed to analyze spectra in both energy windows significant to the system and results are reported with explanations of previous discrepancies. Shown is the fact that Ni both preferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Work on Co x Ni 1Ϫx and Fe x Ni 1Ϫx bulk alloys has shown that in the first case surface segregation can be ignored, 25,26 whereas Fe x Ni 1Ϫx alloys exhibit Ni segregation as Wandelt and Ertl show. 27 Their results indicate a Ni segregation of the order ϳ7%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on Co x Ni 1Ϫx and Fe x Ni 1Ϫx bulk alloys has shown that in the first case surface segregation can be ignored, 25,26 whereas Fe x Ni 1Ϫx alloys exhibit Ni segregation as Wandelt and Ertl show. 27 Their results indicate a Ni segregation of the order ϳ7%.…”
Section: Methodsmentioning
confidence: 99%
“…In 6 we show the comparison of T C (nϭϱ) and published values for T C ͑bulk͒. 16 The first thing to notice is that the highest value for T C (nϭϱ) is 908 K for Fe 25 Ni 75 . Referring to the preceding paragraph we are still within the temperature range for which we expect our empirical scaling formula to work.…”
Section: Magnetism Of Fe X Ni 1؊x Filmsmentioning
confidence: 97%